2021
DOI: 10.1021/acsami.1c14453
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Stimuli-Responsive Coordination Network Linked with Bismuth for Chemiresistive Gas Sensing

Abstract: This paper describes the design, synthesis, characterization, and performance of a novel semiconductive crystalline coordination network, synthesized using 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) ligands interconnected with bismuth ions, toward chemiresistive gas sensing. Bi(HHTP) exhibits two distinct structures upon hydration and dehydration of the pores within the network, Bi(HHTP)-α and Bi(HHTP)-β, respectively, both with unprecedented network topology (2,3-c and 3,4,4,5-c nodal net stoichiometry, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…In addition, the calculated BET surface areas of our Bi (HHTP) nanobelts are much higher than the value of Bi (HHTP) in the reported literature. 29 As mentioned above, the TEM image shows the Bi(HHTP) nanobelts contain many small crystals (Fig. S3 †), and the small open interspaces between the crystals can allow more nitrogen molecules to be adsorbed during the nitrogen adsorption measurement, which could be attributed to the enhancement in specific surface areas.…”
Section: Structural and Physicochemical Characterizationmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition, the calculated BET surface areas of our Bi (HHTP) nanobelts are much higher than the value of Bi (HHTP) in the reported literature. 29 As mentioned above, the TEM image shows the Bi(HHTP) nanobelts contain many small crystals (Fig. S3 †), and the small open interspaces between the crystals can allow more nitrogen molecules to be adsorbed during the nitrogen adsorption measurement, which could be attributed to the enhancement in specific surface areas.…”
Section: Structural and Physicochemical Characterizationmentioning
confidence: 76%
“…S1a,† and the diffraction peaks of the samples agree well with the reported results of the Bi(HHTP) crystals. 29 In addition, a weak peak is observed at the 2 θ position of 6.74°, which corresponds to a very small amount of residual bismuth( iii ) acetate. The amount of residual bismuth( iii ) acetate is estimated to be very low, and its presence in Bi(HHTP) almost has no influence on the electrochemical performance of Bi(HHTP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the same CMOF materials with physical forms have very different properties due to their different microstructures. Moreover, the electrocatalytic and electrochemical sensing properties of the same series of conductive MOFs with different metal atomic centers also differ . For the linkers, a tricatecholate with a highly conjugated structure, 2,3,6,7,10,11-hexahydroxy­triphenylene (H 12 C 18 O 6 , HHTP), is redox-active and capable of reversible interconversions among catecholate, quinone, and semiquinonate, making it have a variety of applications in electrocatalysis, , charge storage, , and chemical resistance sensing. The M 3 (HHTP) 2 nanorod materials based on an electrochemically active metal as the metal center are expected to show high electrocatalytic activity for construction of electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%